Comparison of the fluidized state stability from radioactive particle tracking results - Salierno, Gabriel Leonardo (2021)
Currently, various industrial processes are carried out in fluidized bed reactors. Knowing its internal dynamics is fundamental for the intensification of these processes. This work assesses the motion of fluidized calcium alginate spheres under the influence of an upward fluid flow within a 1.2 m high and 0.1 m inner diameter acrylic column. The liquid–solid fluidized bed was compared with a gas–liquid–solid fluidized bed operation mode in terms of mixing behavior. The radioactive particle tracking technique is a proper methodology to study the internal dynamics of these kinds of equipment. Data gathered were analyzed with Shannon entropy as a dynamic mixing measure. Mixing times were found to be between 1 and 2.5 seconds for both fluidization modes. The liquid– solid fluidized bed presents a rather smooth mixing time profile along the column. On the other hand, the gas–liquid–solid fluidized bed showed high sensitivity of entropy production with height, reaching a sharp tendency break at the second quartile of the column. The Glansdorff–Prigogine stability measure can accurately capture flow regime transitions of the gas–liquid–solid fluidized bed, allowing it to be used to construct reliable operative windows for fluidization equipment.